Comparative Field Studies of Various Traps and Attractants for the Olive Fruit fly, Bαctrocerα oleαe - Haniotakis, G.E.; Broumas, ΤΗ.; Liaropoulos, C. (ENTOMOLOGIA HELLENICA, 1998)
In the framework of an ongoing effort for development of an effective trap for the control of the olive fruit fly, Bactrocera oleae (Gmelin) (Diptera, Tephrifidae), by mass trapping, four trap types (wood, cloth, laminate, McPhail), seven different colors of laminate traps, different food attractants, attractant combinations or formulations (total of ten cases), and two insecticides (deltamethrin, b-cyfluthrin) used as killing agents on the traps, were compared under field conditions. The following conclusions may be drawn: Laminate traps (paper envelopes with a polyethylene lining inside, 15×20 cm in size, containing 70 g of ammonium bicarbonate salt and impregnated with 15 mg (a.i.) of an insecticide), were more effective than wood traps. Effectiveness of laminate traps can be enhanced by using an attracting color or in the case of the food attractant ammonium bicarbonate, by incorporating copper oxychloride. Combinations of two protein hydrolysates were more effective than one hydrolysate alone. Effectiveness of protein hydrolysates is not constantly higher than that of ammonium bicarbonate, the use of which is more economic and convenient. The insecticide b-cyfluthrin may be used on traps instead of deltamethrin, which is known to have a repellent effect on the olive fly, especially Linder high concentrations, and is unstable under natural UV light.